Nitrous oxide emissions from wheat fields: N source, N rate, irrigation, and weather effects - Samantha R. Angeles; Guillermo Hernandez-Ramirez; Brian Beres; Xiying Hao; Jen Owens (European Journal of Agronomy, 2026)

Occurrence of acrylamide and 4-methylimidazole in roasted and ground coffee and the effect of L-asparaginase treatment of green coffee on their levels - David S. da Costa; Edna J. H. Ramirez; Sara R. de Carvalho; Patrícia A. C. Braga; José O. Fernandes; Sara C. Cunha; Adriana P. A. Bragotto (Food Additives & Contaminants: Part A, 2026)

Weaving Indigenous and Western knowledge systems across a continuum of knowledge and decision-making spaces - Natalie C Ban; Hannah V Watkins; Robyn E Forrest; Alejandro Frid; Carrie A Holt; Sierra J Hall; Christina N Service; Luisa Ramirez; Daniel L Curtis; Kyle L Wilson; Lawrence Ignace; Andrea J Reid; et al. (Current Opinion in Environmental Sustainability, 2026)

Effect of sodium bicarbonate on performance and markers of kidney and gastrointestinal injury during repeated sprints in the heat - Jonathan W. Specht; Marissa Ramirez; Jennifer Raef; Mackenzie Schwartz; Alyssa R. Bailly; Oscar Chavez; Ozan Kumbasar; Jade X. Dawson; Jessica Apodaca; Raul Freire; Whitley C. Atkins; Flávio de Castro Magalhães; et al. (European Journal of Applied Physiology, 2026)
Purpose We tested the hypotheses that sodium bicarbonate (SB) supplementation improves performance, reduces markers of acute kidney injury (AKI) risk, and increases markers of acute gastrointestinal injury (AGI) during repeated sprints in the heat. Methods Using a double-blind design, 10 recreationally endurance-trained participants ingested 0.2 g/kg of body weight of SB or placebo before cycling in the heat (dry-bulb: 40 °C, relative humidity: 20%). Exercise bouts included a 22-min warm-up, then 4-sets of 5 × 6-sec maximal-effort standing cycling sprints. Core temperature (Tc) was measured at baseline, end of warm-up, after set two of sprints, and post-exercise bouts. Urine and plasma collected pre-ingestion and pre-, post-, and 1-h post-exercise were analyzed for markers of AKI risk, AGI, and endotoxemia. Results SB increased peak (average difference between conditions: 21 ± 11 W, condition effect: p = 0.02) and average ( p = 0.03) power across the sprints. Tc increased from pre- to post-exercise (placebo: Δ1.3 ± 0.3 °C, SB: Δ1.4 ± 0.4 °C, time effect: p < 0.001), but there were no effects of condition or interaction. Exercise increased the primary marker of AKI (urinary IGFBP7×TIMP-2, time effect: p = 0.005) but not urinary NGAL. There were no condition or interaction effects for either AKI marker. Plasma I-FABP, a marker of AGI, increased post-exercise bouts (placebo: Δ291 ± 550 pg/mL, SB: Δ397 ± 482 pg/mL, p = 0.03), with no condition or interaction effects. There were no significant effects for markers of endotoxemia (LBP, sCD14). Conclusions SB supplementation improves repeat sprint performance in the heat without altering Tc, markers of AKI risk, or markers of AGI.

Place attachment and agroforestry adoption - Alexandra R. Ramirez; Sarah E. Castle; Chloe B. Wardropper (Agroforestry Systems, 2026)
Conventional row crop farming in the United States is associated with multiple environmental challenges including soil and water degradation and decreased biodiversity. Sustainable agriculture advocates have encouraged agroforestry, or the integration of woody perennial crops like trees and shrubs into agricultural systems, to ameliorate environmental challenges and provide on-farm benefits. Despite promised environmental benefits and efforts to increase adoption, rates of agroforestry practice remain low in the US. Researchers have long studied how agricultural decision-making is shaped by psychological, financial, institutional, and logistical challenges, but there is less attention on the role of emotional and cultural factors in the adoption of new agricultural practices. Through interviews with 31 farmers (both adopters and non-adopters of agroforestry) in Illinois, we examine how place attachment, or the cognitive and emotional bonds between people and place, influences the long-term investment decisions associated with agroforestry. We find that place attachment is expressed through distinct dimensions: place dependence, place identity, and place affect. While specific attachments like connection to nature and family legacy often motivate adoption, attachments related to economic dependence on the land and traditional farming identities are sometimes barriers to adoption. Our findings suggest that outreach and extension work on agroforestry may be improved by explicitly acknowledging place-specific values and emotions.

Predictors of worsening food security among women living with and without HIV and seronegative women during COVID-19: a mixed methods study - Jenni M. Wise; Hilary Bethancourt; Torsten B. Neilands; Anna Leddy; Gypsyamber D’Souza; Mirjam-Colette Kempf; Janet M. Turan; Gina Wingood; M. Reuel Friedman; Jennafer Kwait; Lakshmi Goparaju; Mardge Cohen; et al. (Food Security, 2026)
This study aimed to assess the prevalence, severity, predictors, and lived experiences of food insecurity among women enrolled in the Women’s Interagency HIV Study in the USA in 2020, at the height of the COVID-19 pandemic. We hypothesized that pre-existing socioeconomic and health-related disparities would heighten the risk of worsening food insecurity during the pandemic. The 10-item US Household Food Security Survey was administered to participants three times between June and September 2020. Multilevel mixed-effects ordered logistic regression models were used to estimate the odds of worsening food security compared to pre-pandemic baseline data. Qualitative interviews were conducted among a subset of participants to add understanding of the lived experience of food insecurity during the pandemic, beyond what quantitative measures could provide. Among 1,506 women, 28% had marginal to very low food security at baseline, and between 13.6-17.3% experienced worsening food security during pandemic measures. Women with household incomes <$12,000/year were particularly vulnerable to worsening food insecurity, including those experiencing unemployment (OR: 2.06, 95% CI:1.36, 3.13), job loss (OR: 1.47, 95% CI: 1.04-2.06), loss of financial support (OR: 1.91,95% CI: 1.23, 2.97), and those with reduced access to usual sources of food (OR: 7.67, 95% CI:4.78, 12.30). While the quantitative data suggest that relatively few women experienced worsening food security during the pandemic, the qualitative data suggest that many more women had difficulty accessing preferred and healthy foods and experienced disruption to social services, which typically facilitate the ability to access food. Women described how informal social systems (e.g., neighborhood gardens, sharing resources) bridged the gap left by more formal systems during this time. Taken together, these findings suggest that women with pre-existing socioeconomic vulnerability were disproportionately and negatively impacted by the social and economic disruptions of the COVID-19 pandemic. Interventions are needed to address structural vulnerabilities, improve safeguards to food security during times of distress, and harness the capacity of community-based support systems.

Life cycle greenhouse gas emissions of electricity generated from waste coal in the United States - Marie-Odile P. Fortier; Alyssa R. Pfadt-Trilling; Amir Sharafi; Sierra J. Lema; Vasco Ramirez (Resources, Conservation and Recycling, 2026)

Continental‐wide prioritization of protected areas to address global and habitat‐specific goals for avian biodiversity conservation - Yanjie Xu; Diego Pavón‐Jordán; Tyler Hallman; Tristan R. M. Bakx; Lluís Brotons; Sergi Herrando; Alison Johnston; Brett K. Sandercock; Thomas Sattler; Alaaeldin Soultan; Vitalie Ajder; Dawn E. Balmer; et al. (Conservation Biology, 2026)
The United Nations and European Union have set ambitious conservation goals to halt and reverse declines in biodiversity by protecting 30% of land and sea areas by 2030. Effective conservation planning requires evidence‐based spatial prioritization to maximize the coverage of species within designated protected areas. Based on a pan‐European database for occurrence and abundance of breeding birds collected in the 2010s, we applied the Zonation algorithm to identify key areas that would maximize the protection of ranges and populations for 435 species of breeding birds across Europe using either continental or national prioritization targets. When 30% of Europe's highest priority terrestrial areas were selected by the algorithm, 49% of species’ ranges and 63% of species’ populations were protected. When 10% and 30% of the highest priority lands were selected, compared with prioritization using occurrence data, prioritization using abundance data resulted in a higher percentage of species’ populations, especially rare and range‐restricted species, being represented for protected area coverage. Stratifying prioritization by habitat criteria greatly enhanced habitat‐specific conservation efficiency, enabling coverage of over 80% of breeding bird species’ populations in tundra, Mediterranean, and coastal habitats with a selection of 10% of the highest priority areas for each. Our prioritization supports international targets adopted under the Kunming–Montreal Global Biodiversity Framework by identifying key areas and providing a roadmap to guide optimal site protection and conservation planning in Europe.

Antimicrobial 3D printed implants for periprosthetic joint infections - Iván Yuste; Francis C. Luciano; Carmina Rodríguez; Bianca I. Ramirez; Chrysi Rapti; Brayan J. Anaya; Aikaterini Lalatsa; Almudena Ribed-Sánchez; Pablo Sanz-Ruiz; Elena González-Burgos; Dolores R. Serrano (Drug Delivery and Translational Research, 2026)
Periprosthetic joint infections (PJIs) remain a serious complication following hip and knee arthroplasty, affecting 1–5% of patients in developed countries and posing significant challenges to patients, clinicians, and healthcare systems. Conventional prophylactic strategies, such as antibiotic-loaded bone cement, suffer from limited post-implantation drug release and potential compromise of mechanical integrity. To overcome these limitations, we developed a personalized, 3D-printed implant designed to integrate with the acetabular component of joint prostheses. These implants deliver either monotherapy or a combination of amphotericin B (AmB) and vancomycin (VAN), targeting both fungal and bacterial pathogens. Fabricated via fused deposition modeling using a biocompatible polyvinyl alcohol–polyethylene glycol (PVA–PEG) matrix, the implants enable passive drug loading and rapid adhesion to prosthetic surfaces within 60 s, minimizing operative time. In vitro testing confirmed broad-spectrum antimicrobial activity against Candida spp. ( C. albicans , C. parapsilosis , C. glabrata , C. krusei ) and Staphylococcus spp. ( S. aureus , S. epidermidis ). VAN was released rapidly, while AmB exhibited sustained release for up to 10 h, with both maintaining saturation solubility for 48 h. Notably, AmB-loaded implants showed five-fold lower hemolytic toxicity compared to free drug. These results highlight the potential of 3D-printed, drug-eluting implants as a clinically viable solution for the prevention and early treatment of PJIs. Graphical abstract

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Spatial Patterns of Habitat Use of Wintering Tidal Marsh Birds Along the Mississippi Gulf Coast - Carlos Ramirez-Reyes; Kristine O. Evans; Mark S. Woodrey; Rachel Anderson; Jared Feura; Landon R. Jones; Raymond B. Iglay (Wetlands, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Geophysical survey methods (GPR and ERT) to find architectural remains from the 17th century at the Fort of San Diego in Acapulco, Mexico. A case study. - J. Ortega-Ramirez; M. Bano; J.L. Salas-Corrales; R. Junco Sánchez; L.A. Villa-Alvarado (Journal of Applied Geophysics, 2026)

Effects of an intervention for a liquefied petroleum gas cook-stove with free fuel on food insecurity and dietary diversity among women and infants: a multi-country randomized controlled trial - Sheela S. Sinharoy; Rina Das; Anaité Diaz-Artiga; Lisa M. Thompson; Ghislaine Rosa; John McCracken; Miles A. Kirby; Carla Tarazona-Meza; Vigneswari Aravindalochanan; Shirin Jabbarzadeh; Jiantong Wang; Ajay Pillarisetti; et al. (Food Security, 2026)

Seismic classification of rainfall-induced lahars at Volcán de Colima, México: frequency content as an indicator of sediment concentration - V.H. Márquez-Ramirez; L. Capra; J.I. Martínez-Valdés; R. Barroso-Fernández; R. Arámbula-Mendoza; M. González Amezcua; R. García Flores (Journal of South American Earth Sciences, 2025)

Relocated, range-limited, but resilient: niche shift and constraints on spread in introduced Nanday parakeets (Aratinga nenday) - Brenda R. Ramirez; Diego C. Blanco; John E. McCormack (Urban Ecosystems, 2025)
Introduced species often encounter novel environments that test their capacity for ecological flexibility and adaptation. We investigated ecological niche dynamics in Nanday Parakeets ( Aratinga nenday ), a naturalized parrot species in Los Angeles, to assess whether their introduced range reflects a shift from their native range in South America. Using principal components analysis and niche overlap tests, we found that the introduced population occupies a distinct environmental space—cooler, drier, and with less tree cover—with no measurable niche overlap. Habitat suitability modeling in Los Angeles suggests that their current habitat is narrowly concentrated in south-facing coastal canyons and not in more arid inland or high-elevation areas. Data from iNaturalist show that Nanday Parakeets roost and feed mainly in sycamore trees. The 2025 Palisades Fire impacted only 3% of suitable habitat, while the 2018 Woolsey Fire impacted 12%, neither with an observable effect on the population. Our results highlight the contradiction apparent in many species introductions: niche flexibility during establishment combined with ecological constraints on later spread.

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

Household air pollution and blood pressure among adult women participants of the Household Air Pollution Intervention Network Trial: An exposure-response analysis - Ajay Pillarisetti; Wenlu Ye; Jennifer L. Peel; Howard Chang; Lindsay J. Underhill; Kalpana Balakrishnan; Anaité Díaz-Artiga; John P. McCracken; Ghislaine Rosa; Lisa M. Thompson; Vigneswari Aravindalochanan; Dana Boyd Barr; et al. (Environmental Research, 2025)

Gestational and postnatal exposures to fine particulate matter (PM2.5) and their association with acute ear infections, diarrhea, respiratory symptoms, and mortality: A longitudinal study of infants in the multicountry Household Air Pollution Intervention Network (HAPIN) trial - Brandie Banner Shackelford; Kyle Steenland; Miles A. Kirby; Kalpana Balakrishnan; Marilú Chiang; Anaité Diaz-Artiga; John P. McCracken; Lisa M. Thompson; Ghislaine Rosa; Lance A. Waller; Shirin Jabbarzadeh; Jiantong Wang; et al. (Environmental Research, 2025)

Performative planning? Evaluating coexistence and procedural justice in Queensland's gas–agriculture interface - Shay D. Dougall; Josephine Gillespie; Adem Sav; Javier Cortes Ramirez; Melissa R. Haswell (Journal of Rural Studies, 2025)

Toxicity of six representative polycyclic aromatic compounds in five marine test species - Benjamin P. de Jourdan; David L. Daniel; Piero R. Gardinali; Cesar Ramirez; Chris J. Langdon; Emily Stefansson; Thomas F. Parkerton; William A. Stubblefield (Science of The Total Environment, 2025)

Toward a better understanding of curve number and initial abstraction ratio values from a large sample of watersheds perspective - Abderraman R. Amorim Brandão; Dimaghi Schwamback; André Simões Ballarin; John J. Ramirez-Avila; José Goes Vasconcelos Neto; Paulo Tarso S. Oliveira (Journal of Hydrology, 2025)

Subcortical white matter hyperintensities and motor function in parkinson’s disease: findings from the ONDRI study - Daniela Cristina Carvalho de Abreu; Frederico Pieruccini-Faria; Anthony E. Lang; Benjamin Cornish; William McIlroy; Mandar Jog; Mario Masellis; Joel Ramirez; Christopher Scott; Sean Symons; Sandra E. Black; Stephen R. Arnott; et al. (GeroScience, 2025)

Long‐Term Human Land‐Use Change Throughout Southeast Asia Reshapes the Distribution of Suitable Habitat for a Human‐Commensal Bird Species - Brenda R. Ramirez; Jamie M. Kass; Amanda J. Zellmer; Amanda K. Hund; Elizabeth S. C. Scordato (Journal of Biogeography, 2025)
Aim Human activity has reshaped ecological communities for thousands of years. While these activities have typically led to habitat loss, some species have successfully exploited human environments. However, the effects of long‐term human land‐use on the distributions of such species are poorly understood. Here, we investigated how land‐use change over the last 12,000 years has altered habitat distributions for a widespread human‐commensal bird, the Pacific swallow ( Hirundo tahitica ). Location Southeast Asia, Melanesia. Methods We assessed habitat availability for Pacific swallows using citizen science‐based occurrence records and species distribution models that included (a) only climate data, (b) only land‐use data and (c) both variable sets combined. We evaluated approaches to address the unique spatial biases that arise in unstructured survey data of human‐associated species and determined which models performed best with present‐day occurrence records. We then hindcasted alternative models at 1000‐year intervals over 12,000 years to evaluate the relative effects of climate and human land‐use on long‐term habitat availability. Results Models that included both climate and human land‐use variables were the best fit to occurrence records. Standard methods for controlling for spatial bias performed poorly compared with fully sampling the environmental background, highlighting unique considerations for modelling human‐associated species. Hindcasting showed that while climate‐only models predicted little change in habitat availability over time, combined models showed habitat increases beginning more than 5000 years ago and significant expansions of habitat over the last 2000 years. Main Conclusions Human land‐use over the last several thousand years has likely provided Pacific swallows with substantial new habitat, which may have led to population size expansions. Incorporating long‐term human land‐use into species distribution models offers insights into when associations with human environments may have arisen and generates testable predictions for how populations respond and adapt to human land‐use change over millennial timescales.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Cost-effective and stable biosensing of biochemical oxygen demand in wastewater treatment: Exsolved rhodium-titanate perovskite catalyst in microbial fuel cell-based biosensors - Anna Salvian; Shailza Saini; Marina Ramirez-Moreno; Claudio Avignone-Rossa; John R. Varcoe; Kalliopi Kousi; Siddharth Gadkari (Journal of Environmental Chemical Engineering, 2025)

Synoptic patterns of extreme precipitation events in Northeast Brazil - Matheus J. A. Lyra; Helber B. Gomes; Dirceu L. Herdies; Silvio N. Figueroa; Enver Ramirez; José A. Aravéquia; Maria C. L. Silva; Fabricio D. S. Silva; Heliofábio B. Gomes; Eder P. Vendrasco; Leonardo Calvetti; Hugo A. Braga; et al. (Natural Hazards, 2025)

Correction: Sequence Divergence in Venom Genes Within and Between Montane Pitviper (Viperidae: Crotalinae: Cerrophidion) Species is Driven by Mutation–Drift Equilibrium - Ramses Alejandro Rosales‑Garcia; Rhett M. Rautsaw; Erich P. Hofmann; Christoph I. Grünwald; Hector Franz‑Chavez; Ivan T. Ahumada‑Carrillo; Ricardo Ramirez‑Chaparro; Miguel Angel de la Torre‑Loranca; Jason L. Strickland; Andrew J. Mason; Matthew L. Holding; Miguel Borja; et al. (Journal of Molecular Evolution, 2025)

Associations of prenatal maternal psychosocial stress and depression with neurodevelopmental outcomes in 7.5-month-old infants in the ECHO.CA.IL prospective birth cohorts - Nicholas Cragoe; Jenna Sprowles; Stephanie M. Eick; Lynn Harvey; Xavier R. Ramirez; Gloria Arroyo Sugg; Rachel Morello-Frosch; Tracey Woodruff; Susan L. Schantz (Neurotoxicology and Teratology, 2025)

The use of sex-sorted semen in horses - JC Samper; JC Hernandez Aviles; LF Ramirez-Agamez; CC Love; C Gonzalez-Marin; P Fleury; P Dini; A De La Fuente; R Foss; FL Campos; PJ Ross (Journal of Equine Veterinary Science, 2025)

Effect of dietary citrus pulp on performance and dry matter digestibility in dairy cows: A meta-analysis and meta-regression - E.E. Corea-Guillen; M. Benaouda; A.H. Ramirez-Perez; A.C. Lizarazo; J.M. Castro-Montoya; R. Vieyra-Alberto; J.C. Angeles-Hernandez (Animal Feed Science and Technology, 2025)

Tree Diversity Increases Carbon Stocks and Fluxes Above—But Not Belowground in a Tropical Forest Experiment - Florian Schnabel; Joannès Guillemot; Kathryn E. Barry; Melanie Brunn; Simone Cesarz; Nico Eisenhauer; Tobias Gebauer; Nathaly R. Guerrero‐Ramirez; I. Tanya Handa; Chris Madsen; Lady Mancilla; Jose Monteza; et al. (Global Change Biology, 2025)
International commitments advocate large‐scale forest restoration as a nature‐based solution to climate change mitigation through carbon (C) sequestration. Mounting evidence suggests that mixed compared to monospecific planted forests may sequester more C, exhibit lower susceptibility to climate extremes and offer a broader range of ecosystem services. However, experimental studies comprehensively examining the control of tree diversity on multiple C stocks and fluxes above‐ and belowground are lacking. To address this gap, we leverage data from the Sardinilla experiment in Panama, the oldest tropical tree diversity experiment, which features a gradient of one‐, two‐, three‐ and five‐species mixtures of native tree species. Over 16 years, we measured multiple above‐ and belowground C stocks and fluxes, ranging from tree aboveground C, over leaf litter C production, to soil organic carbon (SOC). We show that tree diversity significantly increased aboveground C stocks and fluxes, with a 57% higher gain in aboveground tree C in five‐species mixtures compared to monocultures (35.7 ± 1.8 vs. 22.8 ± 3.4 Mg C ha −1 ) 16 years after planting. In contrast, we observed a net reduction in SOC (on average −11.2 ± 1.1 Mg C ha −1 across diversity levels) and no significant difference in SOC 3 stocks (the predominantly tree‐derived, i.e., C 3 plant‐derived SOC fraction) between five‐species mixtures and monocultures (13.0 ± 0.9 vs. 15.1 ± 1.3 Mg C ha −1 ). Positive tree diversity effects persisted despite repeated climate extremes and strengthened over time for aboveground tree growth. Structural equation models showed that higher tree growth in mixtures enhanced leaf litter and coarse woody debris C fluxes to the soil, resulting in a tightly linked C cycle aboveground. However, we did not observe significant links between above‐ and belowground C stocks and fluxes. Our study elucidates the mechanisms through which higher tree diversity bolsters the climate mitigation potential of tropical forest restoration. Restoration schemes should prioritize mixed over monospecific planted forests.

Intra-cohort cannibalism and aggressive behavior in tropical gar (Atractosteus tropicus) larvae: Effects of stocking density and starvation - C.A. Sepúlveda-Quiroz; C.S. Alvarez-Villagomez; C.A. Álvarez-González; L.D. Jiménez-Martínez; G.M. Pérez-Jiménez; G.G. Asencio-Alcudia; O. Mendoza-Porras; J.F. López-Hernández; A. Pérez-Morales; M.A. Galaviz-Espinoza; D. Tovar-Ramirez; C. Ramírez-Martínez; et al. (Aquaculture, 2024)

Corticotropin releasing hormone receptor 1 in the medial prefrontal cortex mediates aversion resistant alcohol intake - Miranda E. Arnold; Cecelia E. Harber; Lauren A. Beugelsdyk; Ellie B. Decker Ramirez; Grace B. Phillips; Jesse R. Schank (Psychopharmacology, 2024)

Occurrence of modified mycotoxins in Latin America: an up-to-date review - Luisina D. Demonte; Eugenia Cendoya; María J. Nichea; Cindy J. Romero Donato; María L. Ramirez; María R. Repetti (Mycotoxin Research, 2024)

Plasma Copper and Metabolic Syndrome in Mesoamerican Children and Their Parents - Claudia R. Villatoro-Santos; Manuel Ramirez-Zea; Eduardo Villamor (Biological Trace Element Research, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Shake-table testing of a stone masonry building aggregate: overview of blind prediction study - I. Tomić; A. Penna; M. DeJong; C. Butenweg; A. A. Correia; P. X. Candeias; I. Senaldi; G. Guerrini; D. Malomo; B. Wilding; D. Pettinga; M. Spanenburg; et al. (Bulletin of Earthquake Engineering, 2024)
City centres of Europe are often composed of unreinforced masonry structural aggregates, whose seismic response is challenging to predict. To advance the state of the art on the seismic response of these aggregates, the Adjacent Interacting Masonry Structures (AIMS) subproject from Horizon 2020 project Seismology and Earthquake Engineering Research Infrastructure Alliance for Europe (SERA) provides shake-table test data of a two-unit, double-leaf stone masonry aggregate subjected to two horizontal components of dynamic excitation. A blind prediction was organized with participants from academia and industry to test modelling approaches and assumptions and to learn about the extent of uncertainty in modelling for such masonry aggregates. The participants were provided with the full set of material and geometrical data, construction details and original seismic input and asked to predict prior to the test the expected seismic response in terms of damage mechanisms, base-shear forces, and roof displacements. The modelling approaches used differ significantly in the level of detail and the modelling assumptions. This paper provides an overview of the adopted modelling approaches and their subsequent predictions. It further discusses the range of assumptions made when modelling masonry walls, floors and connections, and aims at discovering how the common solutions regarding modelling masonry in general, and masonry aggregates in particular, affect the results. The results are evaluated both in terms of damage mechanisms, base shear forces, displacements and interface openings in both directions, and then compared with the experimental results. The modelling approaches featuring Discrete Element Method (DEM) led to the best predictions in terms of displacements, while a submission using rigid block limit analysis led to the best prediction in terms of damage mechanisms. Large coefficients of variation of predicted displacements and general underestimation of displacements in comparison with experimental results, except for DEM models, highlight the need for further consensus building on suitable modelling assumptions for such masonry aggregates.

Influence of wall-to-floor connections and pounding on pre- and post-diction simulations of a masonry building aggregate tested on a shaking table - N. Bianchini; M. P. Ciocci; F. Solarino; A. Romanazzi; R. Ramirez; J. D’Anna; A. Aşıkoğlu (Bulletin of Earthquake Engineering, 2024)
This paper presents numerical simulations within the frame of the project SERA—AIMS (Seismic Testing of Adjacent Interacting Masonry Structures). The study includes blind pre-diction and post-diction stages. The former was developed before performing the shaking table tests at the laboratory facilities of LNEC (Lisbon), while the latter was carried out once the test results were known. For both, three-dimensional finite element models were prepared following a macro-modelling approach. The structure consisted of a half-scaled masonry aggregate composed by two units with different floor levels. Material properties used for the pre-diction model were based on preliminary tests previously provided to the participants. The masonry constitutive model used for the pre-diction study reproduced classical stress–strain envelope, whereas a more refined model was adopted for the post-diction. After eigenvalue analysis, incremental nonlinear time history analysis was performed under a unique sequence based on the given load protocol to account for damage accumulation. In the post-diction, the numerical model was calibrated on the data recorded during the shaking table tests and nonlinear dynamic analysis repeated under the recorded accelerogram sequence. The interaction between the two units was simulated through interface elements. Moreover, the timber floors were accounted following different strategies: not modelling or considering nonlinear wall-to-floor connections. Advantages and disadvantages are then analysed, comparing the pre-diction and post-diction results with the experimental data. Numerical results differ from the experimental outcomes regarding displacements and interface pounding, although a clear improvement is visible in the post-diction model.

Estimation of macro and micronutrient concentrations in ‘valencia’ orange leaves at different phenological stages using multispectral image analysis and multiple regression - P. P. Gomes de Oliveira; C. A. Da Silva-Junior; J. H. Barron-Zambrano; E. Neri-Ramirez; A. Diaz-Manriquez; E. Osorio-Hernandez; R. Delgado-Martinez (International Journal of Remote Sensing, 2024)

Sex differences in visuospatial cognition- a female advantage in jigsaw puzzle solving - Daniela E. Aguilar Ramirez; Jarrod Blinch; Kurt Robertson; Joseph Opdenaker; Claudia L. R. Gonzalez (Experimental Brain Research, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Attenuated incubation of ethanol-induced conditioned taste aversion in a model of dependence - Lindsey A. Ramirez; Kathryn R. Przybysz; Joseph R. Pitock; E. Margaret Starr; Hyerim Yang; Elizabeth J. Glover (Psychopharmacology, 2024)

Bumble bee responses to climate and landscapes: Investigating habitat associations and species assemblages across geographic regions in the United States of America - Morgan E. Christman; Lori R. Spears; Emily K. Burchfield; William D. Pearse; James P. Strange; Ricardo A. Ramirez (Global Change Biology, 2024)
Bumble bees are integral pollinators of native and cultivated plant communities, but species are undergoing significant changes in range and abundance on a global scale. Climate change and land cover alteration are key drivers in pollinator declines; however, limited research has evaluated the cumulative effects of these factors on bumble bee assemblages. This study tests bumble bee assemblage (calculated as richness and abundance) responses to climate and land use by modeling species‐specific habitat requirements, and assemblage‐level responses across geographic regions. We integrated species richness, abundance, and distribution data for 18 bumble bee species with site‐specific bioclimatic, landscape composition, and landscape configuration data to evaluate the effects of multiple environmental stressors on bumble bee assemblages throughout 433 agricultural fields in Florida, Indiana, Kansas, Kentucky, Maryland, South Carolina, Utah, Virginia, and West Virginia from 2018 to 2020. Distinct east versus west groupings emerged when evaluating species‐specific habitat associations, prompting a detailed evaluation of bumble bee assemblages by geographic region. Maximum temperature of warmest month and precipitation of driest month had a positive impact on bumble bee assemblages in the Corn Belt/Appalachian/northeast, southeast, and northern plains regions, but a negative impact on the mountain region. Further, forest land cover surrounding agricultural fields was highlighted as supporting more rich and abundant bumble bee assemblages. Overall, climate and land use combine to drive bumble bee assemblages, but how those processes operate is idiosyncratic and spatially contingent across regions. From these findings, we suggested regionally specific management practices to best support rich and abundant bumble bee assemblages in agroecosystems. Results from this study contribute to a better understanding of climate and landscape factors affecting bumble bees and their habitats throughout the United States.

Safe plates in the school space: Investigating compliance of food safety standards among school-based food service providers - Realyn Q. Salvador; Charizza Mae T. Borromeo; Gary C. Alnas; Shaira Vita Mae G. Adviento; Alma C. Asuncion; Mark R. Limon; Arnelyn B. Esteban; Aprilyn A. Gajete; Shiela Mae L. Garcia; Jherie-Mae R. Parico; Christian Jay P. Pungtilan; Jaypee Carl D. Respicio; et al. (Food and Humanity, 2024)

Comparing environmental impacts of deep‐seabed and land‐based mining: A defensible framework - A. Metaxas; C. D. Anglin; A. Cross; J. Drazen; M. Haeckel; G. Mudd; C. R. Smith; S. Smith; P. P. E. Weaver; L. Sonter; D. J. Amon; P. D. Erskine; et al. (Global Change Biology, 2024)
The crises of climate change and biodiversity loss are interlinked and must be addressed jointly. A proposed solution for reducing reliance on fossil fuels, and thus mitigating climate change, is the transition from conventional combustion‐engine to electric vehicles. This transition currently requires additional mineral resources, such as nickel and cobalt used in car batteries, presently obtained from land‐based mines. Most options to meet this demand are associated with some biodiversity loss. One proposal is to mine the deep seabed, a vast, relatively pristine and mostly unexplored region of our planet. Few comparisons of environmental impacts of solely expanding land‐based mining versus extending mining to the deep seabed for the additional resources exist and for biodiversity only qualitative. Here, we present a framework that facilitates a holistic comparison of relative ecosystem impacts by mining, using empirical data from relevant environmental metrics. This framework (Environmental Impact Wheel) includes a suite of physicochemical and biological components, rather than a few selected metrics, surrogates, or proxies. It is modified from the “recovery wheel” presented in the International Standards for the Practice of Ecological Restoration to address impacts rather than recovery. The wheel includes six attributes (physical condition, community composition, structural diversity, ecosystem function, external exchanges and absence of threats). Each has 3–5 sub attributes, in turn measured with several indicators. The framework includes five steps: (1) identifying geographic scope; (2) identifying relevant spatiotemporal scales; (3) selecting relevant indicators for each sub‐attribute; (4) aggregating changes in indicators to scores; and (5) generating Environmental Impact Wheels for targeted comparisons. To move forward comparisons of land‐based with deep seabed mining, thresholds of the indicators that reflect the range in severity of environmental impacts are needed. Indicators should be based on clearly articulated environmental goals, with objectives and targets that are specific, measurable, achievable, relevant, and time bound.

β-keto amyrin isolated from Cryptostegia grandiflora R. br. inhibits inflammation caused by Daboia russellii viper venom: Direct binding of β-keto amyrin to phospholipase A2 - K.H. Santhosh; V. Krishna; K. Kemparaju; H. Manjunatha; R. Shashi Kumar; A. Mukherjee; S.E. Gomez Mejiba; D.C. Ramirez; B.S. Ravindranath (Toxicon, 2024)

Ecology and management of the coffee berry borer (Hypothenemus hampei): the potential of biological control - Natalia Moreno-Ramirez; Felix J. J. A. Bianchi; Maria R. Manzano; Marcel Dicke (BioControl, 2024)
Coffee is an important commodity in Latin America that is grown by smallholder farmers and large-scale coffee producers. The coffee berry borer, Hypothenemus hampei Ferrari (Coleoptera: Curculionidae: Scolytinae) is a major pest of coffee that originates from West Africa and has invaded all coffee-producing regions. With climate change, the problems that this beetle poses to coffee production are expected to increase. Controlling this pest is a true challenge and chemical insecticides still are one of the main tools used, despite the environmental and human-health issues associated with this approach. To find sustainable alternatives for chemical control of the coffee berry borer, classical biological control, augmentative biological control, and integrated pest management have received extensive attention. Parasitoids, predators, entomopathogenic fungi, and nematodes have been identified and studied for their potential to manage the infestations of this major coffee pest. Conservation biological control has recently gained more attention, but its development is still in its infancy. In this review, we examine strategies for the control of the coffee berry borer in Latin America. We identify knowledge gaps for developing sustainable biological control programs, including conservation biological control within the context of farming systems, land use in the surrounding landscape, as well as the vision of coffee growers.

Experience with extreme weather events increases willingness-to-pay for climate mitigation policy - Rachelle K. Gould; Trisha R. Shrum; Donna Ramirez Harrington; Virginia Iglesias (Global Environmental Change, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Lab-scale engineered hydrochar production and techno-economic scaling-up analysis - Kannan Nadarajah; Oscar M. Rodriguez-Narvaez; Jerome Ramirez; Erick R. Bandala; Ashantha Goonetilleke (Waste Management, 2024)

Individual Variation in Male Pheromone Production in Xylocopa sonorina Correlates with size and Gland Color - Andrew J. Goffinet; Kathy Darragh; Nicholas Saleh; Madeleine M. Ostwald; Stephen L. Buchmann; Santiago R. Ramirez (Journal of Chemical Ecology, 2024)

Canary in the forest?—Tree mortality and canopy dieback of western redcedar linked to drier and warmer summers - R. A. Andrus; L. R. Peach; A. R. Cinquini; B. Mills; J. T. Yusi; C. Buhl; M. Fischer; B. A. Goodrich; J. M. Hulbert; A. Holz; A. J. H. Meddens; K. B. Moffett; et al. (Journal of Biogeography, 2024)
Aim Forest dieback is increasing from unfavourable climate conditions. Western redcedar (WRC)—a culturally, ecologically and economically important species—has recently experienced anomalously high mortality rates and partial canopy dieback. We investigated how WRC tree growth and dieback responded to climate variability and drought using tree‐ring methods. Location Pacific Northwest, USA. Taxon Western redcedar ( Thuja plicata ). Methods We collected tree cores from three tree health status groups (no canopy dieback, partial canopy dieback, and dead trees) at 11 sites in coastal (maritime climate) and interior (continental climate) WRC populations. From growth rates, we computed four growth indices that assessed the resilience to drought and estimated the year of death. Results Warmer and drier climate conditions in May/June that extended the annual July‐to‐September dry season reduced radial growth in 9 of 11 sites (1975–2020). WRC trees recovered growth to pre‐drought rates within 3 years when post‐drought climate conditions were cooler/wetter than average. However, recovery from drought was slower or absent when warmer/drier conditions occurred during the post‐drought recovery period, possibly leading to the recent and widespread mortality across the coastal population. WRC mortality was portended by 4–5 years of declining growth. Annually‐resolved mortality in coastal populations predominately occurred in 2017–2018 (80% of sampled dead trees), a period that coincided with exceedingly hot temperatures and the longest regionally dry period from May to September (1970–2020). In interior populations, mortality was dispersed among years but associated with warmer and drier conditions from August to September. Main conclusions Our findings forewarn that a warming climate and more frequent and severe summer droughts, especially in consecutive years, will likely increase the vulnerability of WRC to canopy dieback and mortality and possibly other drought‐sensitive trees in one of the world's largest forest carbon sinks.

Evaluating Participant Recipe Changes in a Healthy Meal Kit Intervention for Families with Low Income - E. McNulty; K. Chambers; R. Zambrano; I. Ramirez; A. Mitchell; L. House; A. Mathews; K. Shelnutt (Journal of the Academy of Nutrition and Dietetics, 2023)

Uranium supply potential from imported phosphate rocks for the Philippine nuclear power program - Reymar R. Diwa; Jennyvi D. Ramirez; Nils H. Haneklaus (The Extractive Industries and Society, 2023)

Effect of pelleting on the enzymatic digestibility of corn stover - Xueli Chen; Antonio C. Freitas dos Santos; Diana M. Ramirez Gutierrez; Peiyuan Song; John E. Aston; David N. Thompson; James H. Dooley; Michael R. Ladisch; Nathan S. Mosier (Bioresource Technology, 2023)

Phosphogypsum circular economy considerations: A critical review from more than 65 storage sites worldwide - Essaid Bilal; Hajar Bellefqih; Véronique Bourgier; Hamid Mazouz; Delia-Georgeta Dumitraş; Frédéric Bard; Marie Laborde; Jean Pierre Caspar; Bernard Guilhot; Elena-Luisa Iatan; Moussa Bounakhla; Măruţa Aurora Iancu; et al. (Journal of Cleaner Production, 2023)

Soil moisture and vapor pressure deficit controls of longleaf pine physiology: results from a throughfall reduction study - Caren C. Mendonca; Lisa J. Samuelson; Tom A. Stokes; Michael R. Ramirez; Carlos Gonzalez-Benecke; Michael J. Aspinwall (Trees, 2023)

Sequence Divergence in Venom Genes Within and Between Montane Pitviper (Viperidae: Crotalinae: Cerrophidion) Species is Driven by Mutation–Drift Equilibrium - Ramses Alejandro Rosales-García; Rhett M. Rautsaw; Erich P. Hofmann; Christoph I. Grünwald; Hector Franz-Chavez; Ivan T. Ahumada-Carrillo; Ricardo Ramirez-Chaparro; Miguel Angel de la Torre-Loranca; Jason L. Strickland; Andrew J. Mason; Matthew L. Holding; Miguel Borja; et al. (Journal of Molecular Evolution, 2023)

The p,p’-DDE disturbs the M1 function without affecting the M2 phenotype nor unstimulated bone marrow-derived macrophages from BALB/c mice - Vanessa Cortés-Montoya; Christian D. Ortiz-Robles; Omar B. Rivera-Maya; José R. Palacios-Valladares; Erick F. Ramirez-Gutierrez; Emma S. Calderón-Aranda (Toxicology, 2023)

PlantACT! – how to tackle the climate crisis - Heribert Hirt; Salim Al-Babili; Marilia Almeida-Trapp; Antoine Martin; Manuel Aranda; Dorothea Bartels; Malcolm Bennett; Ikram Blilou; Damian Boer; Alix Boulouis; Chris Bowler; Sophie Brunel-Muguet; et al. (Trends in Plant Science, 2023)

Heat stress promotes adaptive physiological responses and alters mrna expression of ruminal epithelium markers in Bos taurus indicus cattle fed low- or high-energy diets - Javier A.M. Meneses; Olavo A.A.L. de Sá; German D. Ramirez-Zamudio; Karolina B. Nascimento; Tathyane R.S. Gionbelli; Matheus H. Luz; Márcio M. Ladeira; Daniel R. Casagrande; Mateus P. Gionbelli (Journal of Thermal Biology, 2023)

Modeling slash pine mortality rates incorporating responses to silvicultural treatments and fusiform rust infection rates - Laura Ramirez; Cristian R. Montes; Bronson P. Bullock (Forest Ecology and Management, 2023)

Lessons learned in knowledge co-production for climate-smart decision-making - Alyssa Rosemartin; Theresa M. Crimmins; Katharine L. Gerst; Erin E. Posthumus; Aaron R. Ramirez; Cynthia SA Wallace; Toni Lyn Morelli (Environmental Science & Policy, 2023)

Molecular markers for thermo-tolerance are associated with reproductive and physiological traits in Pelibuey ewes raised in a semiarid environment - Candelario A. Castillo-Salas; Guillermo Luna-Nevárez; Javier R. Reyna-Granados; Rosa I. Luna-Ramirez; Sean W. Limesand; Pablo Luna-Nevárez (Journal of Thermal Biology, 2023)

Economic analysis of the benefits to petroleum refiners for low carbon boosted spark ignition biofuels - Nicholas A. Carlson; Avantika Singh; Michael S. Talmadge; Yuan Jiang; George G. Zaimes; Shuyun Li; Troy R. Hawkins; Lauren Sittler; Aaron Brooker; Daniel J. Gaspar; Robert L. McCormick; M.M. Ramirez-Corredores (Fuel, 2023)

Economic and environmental analysis to evaluate the potential value of co-optima diesel bioblendstocks to petroleum refiners - Yuan Jiang; George G. Zaimes; Shuyun Li; Troy R. Hawkins; Avantika Singh; Nicholas Carlson; Michael Talmadge; Daniel J. Gaspar; M.M. Ramirez-Corredores; Andrew W. Beck; Ben Young; Lauren Sittler; et al. (Fuel, 2023)

Simulation of moisture transport in fired-clay brick masonry structures accounting for interfacial phenomena - R. Ramirez; B. Ghiassi; P. Pineda; P.B. Lourenço (Building and Environment, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

A workplace wellness program at an academic health center influences employee health, satisfaction, productivity and the rate of workplace injury - Paul T. Rubery; Gabriel Ramirez; Charles R. D’Agostino; Kostantinos Vasalos; Caroline Thirukumaran (International Archives of Occupational and Environmental Health, 2022)

A First Record of Organochlorine Pesticides in Barn Owls (Tyto alba) from Portugal: Assessing Trends from Variation in Feather and Liver Concentrations - I. Roque; R. Lourenço; A. Marques; E. Martínez-López; S. Espín; P Gómez-Ramirez; A. J. García-Fernández; A. Roulin; J. E. Rabaça (Bulletin of Environmental Contamination and Toxicology, 2022)

Circulating concentrations of free triiodothyronine are associated with central adiposity and cardiometabolic risk factors in young euthyroid adults - Elisa Merchan-Ramirez; Guillermo Sanchez-Delgado; Cristina Arrizabalaga-Arriazu; Francisco M Acosta; Maria Jose Arias-Tellez; Manuel Muñoz-Torres; Jose V Garcia-Lario; Jose M Llamas-Elvira; Jonatan R Ruiz (Journal of Physiology and Biochemistry, 2022)
Thyroid dysfunction is associated with classic cardiometabolic risk factors in humans. However, this relationship remains unclear in young euthyroid adults. The present work examines the associations of circulating thyroid hormones (THs) and thyroid-stimulating hormone (TSH) concentrations with body composition and cardiometabolic risk factors in young euthyroid adults. A total of 106 sedentary, euthyroid adults (72 women; 22 ± 2 years old) participated in this cross-sectional study. THs and TSH serum concentrations were determined in fasting conditions (6 h). Body composition (fat mass (FM), lean mass (LM), and visceral adipose tissue (VAT)) was determined by dual-energy X-ray absorptiometry, anthropometric parameters (weight, height, and waist circumference) were measured, and neck adipose tissue mass was quantified through computed tomography (CT) scanning. Cardiometabolic risk factors including fasting glucose and lipid metabolism markers, hepatic phosphatase and transaminases, and blood pressure were also assessed. Free triiodothyronine (FT3) concentration was positively associated with body mass index, LM, VAT, and waist circumference (all P ≤ 0.038). FT3 was also associated with glucose, insulin, HOMA-IR, fatty liver index, and blood pressure (all P < 0.024). All the associations were attenuated when adjusting for sex. In contrast, we found no associations of TSH or free thyroxine with any body composition parameter or cardiometabolic risk factors. In conclusion, FT3 is associated with central adiposity and cardiometabolic risk factors including insulin resistance, fatty liver index, and mean, systolic and diastolic blood pressure in young euthyroid adults. ClinicalTrials.gov identifier: NCT02365129.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

SGLT2 inhibition attenuates arterial dysfunction and decreases vascular F-actin content and expression of proteins associated with oxidative stress in aged mice - Rogerio N. Soares; Francisco I. Ramirez-Perez; Francisco J. Cabral-Amador; Mariana Morales-Quinones; Christopher A. Foote; Thaysa Ghiarone; Neekun Sharma; Gavin Power; James A. Smith; R. Scott Rector; Luis A. Martinez-Lemus; Jaume Padilla; et al. (GeroScience, 2022)
Aging of the vasculature is characterized by endothelial dysfunction and arterial stiffening, two key events in the pathogenesis of cardiovascular disease (CVD). Treatment with sodium glucose transporter 2 (SGLT2) inhibitors is now known to decrease cardiovascular morbidity and mortality in type 2 diabetes. However, whether SGLT2 inhibition attenuates vascular aging is unknown. We first confirmed in a cohort of adult subjects that aging is associated with impaired endothelial function and increased arterial stiffness and that these two variables are inversely correlated. Next, we investigated whether SGLT2 inhibition with empagliflozin (Empa) ameliorates endothelial dysfunction and reduces arterial stiffness in aged mice with confirmed vascular dysfunction. Specifically, we assessed mesenteric artery endothelial function and stiffness (via flow-mediated dilation and pressure myography mechanical responses, respectively) and aortic stiffness (in vivo via pulse wave velocity and ex vivo via atomic force microscopy) in Empa-treated (14 mg/kg/day for 6 weeks) and control 80-week-old C57BL/6 J male mice. We report that Empa-treated mice exhibited improved mesenteric endothelial function compared with control, in parallel with reduced mesenteric artery and aortic stiffness. Additionally, Empa-treated mice had greater vascular endothelial nitric oxide synthase activation, lower phosphorylated cofilin, and filamentous actin content, with downregulation of pathways involved in production of reactive oxygen species. Our findings demonstrate that Empa improves endothelial function and reduces arterial stiffness in a preclinical model of aging, making SGLT2 inhibition a potential therapeutic alternative to reduce the progression of CVD in older individuals. Graphical abstract

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Contribution of warm habitat to cold‐water fisheries - Nick Hahlbeck; William R. Tinniswood; Matthew R. Sloat; Jordan D. Ortega; Matthew A. Wyatt; Mark E. Hereford; Ben S. Ramirez; David A. Crook; Kara J. Anlauf‐Dunn; Jonathan B. Armstrong (Conservation Biology, 2022)
A central tenet of landscape ecology is that mobile species depend on complementary habitats, which are insufficient in isolation, but combine to support animals through the full annual cycle. However, incorporating the dynamic needs of mobile species into conservation strategies remains a challenge, particularly in the context of climate adaptation planning. For cold‐water fishes, it is widely assumed that maximum temperatures are limiting and that summer data alone can predict refugia and population persistence. We tested these assumptions in populations of redband rainbow trout ( Oncorhynchus mykiss newberrii ) in an arid basin, where the dominance of hot, hyperproductive water in summer emulates threats of climate change predicted for cold‐water fish in other basins. We used telemetry to reveal seasonal patterns of movement and habitat use. Then, we compared contributions of hot and cool water to growth with empirical indicators of diet and condition (gut contents, weight–length ratios, electric phase angle, and stable isotope signatures) and a bioenergetics model. During summer, trout occurred only in cool tributaries or springs ( 25 °C). During spring and fall, ≥65% of trout migrated to the lake (5–50 km) to forage. Spring and fall growth (mean [SD] 0.58% per day [0.80%] and 0.34 per day [0.55%], respectively) compensated for a net loss of energy in cool summer refuges (–0.56% per day [0.55%]). In winter, ≥90% of trout returned to tributaries (25–150 km) to spawn. Thus, although perennially cool tributaries supported thermal refuge and spawning, foraging opportunities in the seasonally hot lake ultimately fueled these behaviors. Current approaches to climate adaptation would prioritize the tributaries for conservation but would devalue critical foraging habitat because the lake is unsuitable and unoccupied during summer. Our results empirically demonstrate that warm water can fuel cold‐water fisheries and challenge the common practice of identifying refugia based only on summer conditions.

Differential effects of aging on spatial abilities - Daniela E. Aguilar Ramirez; Jarrod Blinch; Kate Takeda; Jennifer L. Copeland; Claudia L. R. Gonzalez (Experimental Brain Research, 2022)

Mapping the Cerebellar Cognitive Affective Syndrome in Patients with Chronic Cerebellar Strokes - Amanda Chirino-Pérez; Oscar René Marrufo-Meléndez; José Ignacio Muñoz-López; Carlos R. Hernandez-Castillo; Gabriel Ramirez-Garcia; Rosalinda Díaz; Lilia Nuñez-Orozco; Juan Fernandez-Ruiz (The Cerebellum, 2022)

Geotechnical zonation and soil–structure interaction at Puerto Vallarta, México - Christian R. Escudero; Alejandro Ramirez Gaytan; Araceli Zamora Camacho; Adolfo Preciado; Karen L. Flores; Adan Gomez Hernandez (Natural Hazards, 2022)

Anti-oxidant and anti-inflammatory effect of polar extracts obtained from waste product of wine making - M. J. Germanó; M. D. Muñoz; M. C. Della-Vedova; G. E. Feresin; M. Rinaldi-Tosi; R. D. Enriz; D. C. Ramirez; F. A. Giannini (Natural Product Research, 2021)

The PMEL gene and merle (dapple) in the dachshund: cryptic, hidden, and mosaic variants demonstrate the need for genetic testing prior to breeding - Blake C. Ballif; Lisa J. Emerson; Christina J. Ramirez; Casey R. Carl; Kyle Sundin; Helen Flores-Smith; Lisa G. Shaffer (Human Genetics, 2021)

Effect of Serum Albumin, a Component of Human Pleural Fluid, on Transcriptional and Phenotypic Changes on Acinetobacter baumannii A118 - Casin Le; Camila Pimentel; Marisel R. Tuttobene; Tomas Subils; Krisztina M. Papp-Wallace; Robert A. Bonomo; Luis A. Actis; Marcelo E. Tolmasky; Maria Soledad Ramirez (Current Microbiology, 2021)

Fine-scale time series surveys reveal new insights into spatio-temporal trends in coral cover (2002–2018), of a coral reef on the Southern Great Barrier Reef - Chris Roelfsema; Eva M. Kovacs; Julie Vercelloni; Kathryn Markey; Alberto Rodriguez-Ramirez; Sebastian Lopez-Marcano; Manuel Gonzalez-Rivero; Ove Hoegh-Guldberg; Stuart R. Phinn (Coral Reefs, 2021)

Corrigendum: Marine Genetic Resources in Areas Beyond National Jurisdiction: Promoting Marine Scientific Research and Enabling Equitable Benefit Sharing - Alex D. Rogers; Amy Baco; Elva Escobar-Briones; Duncan Currie; Kristina Gjerde; Judith Gobin; Marcel Jaspars; Lisa Levin; Katrin Linse; Muriel Rabone; Eva Ramirez-Llodra; Javier Sellanes; et al. (Frontiers in Marine Science, 2021)

Marine Genetic Resources in Areas Beyond National Jurisdiction: Promoting Marine Scientific Research and Enabling Equitable Benefit Sharing - Alex D. Rogers; Amy Baco; Elva Escobar-Briones; Duncan Currie; Kristina Gjerde; Judith Gobin; Marcel Jaspars; Lisa Levin; Katrin Linse; Muriel Rabone; Eva Ramirez-Llodra; Javier Sellanes; et al. (Frontiers in Marine Science, 2021)
Growing human activity in areas beyond national jurisdiction (ABNJ) is driving increasing impacts on the biodiversity of this vast area of the ocean. As a result, the United Nations General Assembly committed to convening a series of intergovernmental conferences (IGCs) to develop an international legally-binding instrument (ILBI) for the conservation and sustainable use of marine biological diversity of ABNJ [the biodiversity beyond national jurisdiction (BBNJ) agreement] under the United Nations Convention on the Law of the Sea. The BBNJ agreement includes consideration of marine genetic resources (MGR) in ABNJ, including how to share benefits and promote marine scientific research whilst building capacity of developing states in science and technology. Three IGCs have been completed to date with the fourth delayed by the Covid pandemic. This delay has allowed a series of informal dialogues to take place between state parties, which have highlighted a number of areas related to MGR and benefit sharing that require technical guidance from ocean experts. These include: guiding principles on the access and use of MGR from ABNJ; the sharing of knowledge arising from research on MGR in ABNJ; and capacity building and technology transfer for developing states. In this paper, we explain what MGR are, the methods required to collect, study and archive them, including data arising from scientific investigation. We also explore the practical requirements of access by developing countries to scientific cruises, including the sharing of data, as well as participation in research and development on shore whilst promoting rather than hindering marine scientific research. We outline existing infrastructure and shared resources that facilitate access, research, development, and benefit sharing of MGR from ABNJ; and discuss existing gaps. We examine international capacity development and technology transfer schemes that might facilitate or complement non-monetary benefit sharing activities. We end the paper by highlighting what the ILBI can achieve in terms of access, utilization, and benefit sharing of MGR and how we might future-proof the BBNJ Agreement with respect to developments in science and technology.

Applications of machine learning algorithms for biological wastewater treatment: Updates and perspectives - Batsuren Sundui; Olga Alejandra Ramirez Calderon; Omar M. Abdeldayem; Jimena Lázaro-Gil; Eldon R. Rene; Uyanga Sambuu (Clean Technologies and Environmental Policy, 2021)

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Regional environmental drivers of Kemp’s ridley sea turtle somatic growth variation - Matthew D. Ramirez; Larisa Avens; Lisa R. Goshe; Melissa L. Snover; Melissa Cook; Heather L. Haas; Selina S. Heppell (Marine Biology, 2020)

An evaluation of visuospatial skills using hands-on tasks - Daniela E. Aguilar Ramirez; Jarrod Blinch; Claudia L. R. Gonzalez (Experimental Brain Research, 2020)

Immature ticks on wild birds and the molecular detection of a novel Rickettsia strain in the Ibitipoca State Park, southeastern Brazil - Diego G. Ramirez; Hermes R. Luz; Sebastián Muñoz-Leal; Walter Flausino; Igor C. L. Acosta; Thiago F. Martins; Maristela Peckle; Helio F. Santos; Guilherme P. Furusawa; Marcelo B. Labruna; João L. H. Faccini (Experimental and Applied Acarology, 2020)

Regional Variation in Kemp’s Ridley Sea Turtle Diet Composition and Its Potential Relationship With Somatic Growth - Matthew D. Ramirez; Larisa Avens; Lisa R. Goshe; Melissa L. Snover; Melissa Cook; Selina S. Heppell (Frontiers in Marine Science, 2020)

Numerical simulation of 1-D oil and water displacements in petroleum reservoirs using the correction procedure via reconstruction (CPR) method - G. Galindez-Ramirez; D. K. E. Carvalho; P. R. M. Lyra (Computational Geosciences, 2020)

Assessing the feasibility of using a closed landfill for agricultural graze land - Hanna R. Hard; Mark Brusseau; Mónica Ramirez-Andreotta (Environmental Monitoring and Assessment, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

A morphological database for Colombian anuran species from conservation‐priority ecosystems - Angela M. Mendoza‐Henao; Ángela M. Cortes‐Gomez; Mailyn A. Gonzalez; Oscar Dario Hernandez‐Córdoba; Andres R. Acosta‐Galvis; Fernando Castro‐Herrera; Juan M. Daza; Julio Mario Hoyos; Martha Patricia Ramirez‐Pinilla; Nicolás Urbina‐Cardona; Beatriz Salgado‐Negret (Ecology, 2019)
Species traits provide a strong link between an organism's fitness and processes at community and ecosystem levels. However, such data remain scarce for amphibians in the Neotropics. Colombia is the country with the highest number of threatened amphibians and the second greatest number of amphibian species worldwide. We present a data set containing eight morphological traits for 4,623 museum specimens of the seven largest collections in the country corresponding to 293 species of 14 families. The number of measured specimens per species ranged from 1 to 118 individuals with a median of 8 individuals per species. Overall, this database gathered morphological information for 37.6% of Colombian anuran diversity. Species measured were mainly distributed in the high Andean forest, the páramo, and wetland ecosystems, and was part of a national initiative led by the Instituto Alexander von Humboldt. The morphological traits were selected on the basis of their role in species’ responses to environmental variability and their contributions to ecosystem processes. These traits were related to habitat use, (forearm length, tibia length, femur length, foot length, and foot webbing), predation and food chains (head width and mouth width), and nutrient recycling (snout–vent length). We expect this data set will be used in studies on functional diversity in amphibians and the development of conservation planning for these taxa. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Adenovirus 5 produces obesity and adverse metabolic, morphological, and functional changes in the long term in animals fed a balanced diet or a high-fat diet: a study on hamsters - Daniel A. Montes-Galindo; Ana C. Espiritu-Mojarro; Valery Melnikov; Norma A. Moy-López; Alejandro D. Soriano-Hernandez; Hector R. Galvan-Salazar; Jorge Guzman-Muñiz; Jose Guzman-Esquivel; Margarita L. Martinez-Fierro; Iram P. Rodriguez-Sanchez; Brenda Paz-Michel; Sergio A. Zaizar-Fregoso; et al. (Archives of Virology, 2019)

Chromosomal polymorphism and molecular variability in the pearly razorfish Xyrichtys novacula (Labriformes, Labridae): taxonomic and biogeographic implications - Mauro Nirchio; Juan Ignacio Gaviria; Zoila R. Siccha-Ramirez; Claudio Oliveira; Fausto Foresti; Valentina Milana; Anna Rita Rossi (Genetica, 2019)

Serum P-glycoprotein level: a potential biomarker of DMARD failure in patients with rheumatoid arthritis - E. E. Perez-Guerrero; L. Gonzalez-Lopez; J. F. Muñoz-Valle; J. C. Vasquez-Jimenez; M. Ramirez-Villafaña; E. N. Sanchez-Rodriguez; S. R. Gutierrez-Ureña; S. Cerpa-Cruz; E. A. Aguilar-Chavez; E. G. Cardona-Muñoz; M. L. Vazquez-Villegas; A. M. Saldaña-Cruz; et al. (Inflammopharmacology, 2018)

Thrombospondin-1 interactions regulate eicosanoid metabolism and signaling in cancer-related inflammation - Manuel U. Ramirez; Elizabeth R. Stirling; Nancy J. Emenaker; David D. Roberts; David R. Soto-Pantoja (Cancer and Metastasis Reviews, 2018)

Discovery of Transcription Factors Novel to Mouse Cerebellar Granule Cell Development Through Laser-Capture Microdissection - Peter G. Y. Zhang; Joanna Yeung; Ishita Gupta; Miguel Ramirez; Thomas Ha; Douglas J. Swanson; Sayaka Nagao-Sato; Masayoshi Itoh; Hideya Kawaji; Timo Lassmann; Carsten O. Daub; Erik Arner; et al. (The Cerebellum, 2018)

The nitrone spin trap 5,5-dimethyl-1-pyrroline N-oxide dampens lipopolysaccharide-induced transcriptomic changes in macrophages - M. D. Muñoz; M. C. Della Vedova; P. R. Bushel; D. Ganini da Silva; R. P. Mason; Z. Zhai; S. E. Gomez Mejiba; D. C. Ramirez (Inflammation Research, 2018)

The anatomy of a pyroclastic density current: the 10 July 2015 event at Volcán de Colima (Mexico) - L. Capra; R. Sulpizio; V. H. Márquez-Ramirez; V. Coviello; D. M. Doronzo; R. Arambula-Mendoza; S. Cruz (Bulletin of Volcanology, 2018)

Urinary excretion of ciprofloxacin after administration of extended release tablets in healthy volunteers. Swellable drug-polyelectrolyte matrix versus bilayer tablets - M. L. Guzmán; C. B. Romañuk; M. F. Sanchez; L. C. Luciani Giacobbe; L. P. Alarcón-Ramirez; F. D. Battistini; F. L. Alovero; A. F. Jimenez-Kairuz; R. H. Manzo; María Eugenia Olivera (Drug Delivery and Translational Research, 2018)

Allelopathic effects of exogenous phenylalanine: a comparison of four monocot species - Barbara R. Evans; Garima Bali; Art Ragauskas; Riddhi Shah; Hugh O’Neill; Cory Howard; Fayola Lavenhouse; Dawn Ramirez; Kelly Weston; Kelly Ramey; Valerie Cangemi; Brian Kinney; et al. (Planta, 2017)

Ventilator-associated pneumonia by methicillin-susceptible Staphylococcus aureus: do minimum inhibitory concentrations to vancomycin and daptomycin matter? - J. Ruiz-Ramos; P. Vidal-Cortés; A. Díaz-Lamas; R. Reig-Valero; F. Roche-Campo; M. Del Valle-Ortiz; X. Nuvials-Casals; M. Ortiz-Piquer; D. Andaluz-Ojeda; L. Tamayo-Lomas; M. A. Blasco-Navalpotro; M. Rodriguez-Aguirregabiria; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Comparative study of As, Cd, Cu, Cr, Mg, Mn, Ni, Pb and Zn concentrations between sediment and water from estuary and port - I. Bejarano-Ramirez; Jose M. Jurado; R. Muñiz-Valencia; Á. Alcázar; Silvia G. Ceballos-Magaña; A. Olivos-Ortiz; O. Rangel (International Journal of Environmental Science and Technology, 2017)

Growth dynamics of juvenile loggerhead sea turtles undergoing an ontogenetic habitat shift - Matthew D. Ramirez; Larisa Avens; Jeffrey A. Seminoff; Lisa R. Goshe; Selina S. Heppell (Oecologia, 2017)

Response of young bearing olive trees to irrigation-induced salinity - A. Ben-Gal; I. Beiersdorf; U. Yermiyahu; N. Soda; E. Presnov; I. Zipori; R. Ramirez Crisostomo; A. Dag (Irrigation Science, 2017)

Degradation of Orange II by Fenton reaction using ilmenite as catalyst - A. Y. Pataquiva-Mateus; H. R. Zea; J. H. Ramirez (Environmental Science and Pollution Research, 2017)

Sedimentary oxygen dynamics in a seasonally hypoxic basin - Dorina Seitaj; Fatimah Sulu‐Gambari; Laurine D. W. Burdorf; Alicia Romero‐Ramirez; Olivier Maire; Sairah Y. Malkin; Caroline P. Slomp; Filip J. R. Meysman (Limnology and Oceanography, 2017)
Seasonal hypoxia refers to the oxygen depletion that occurs in summer in the bottom water of stratified systems, and is increasingly observed in coastal areas worldwide. The process induces a seasonal cycle on the biogeochemistry of the underlying sediments, which remains poorly quantified. Here, we investigated the sedimentary oxygen consumption within Lake Grevelingen (The Netherlands), a saline coastal reservoir that is impacted by yearly recurrent bottom water hypoxia. Monthly sampling campaigns were conducted throughout 2012 at three sites along a depth gradient. Macrofauna sampling and sediment profile imaging demonstrated how summer hypoxia strongly impacts the benthic communities below 15 m of water depth. Benthic fluxes of oxygen, dissolved inorganic carbon, total alkalinity, and ammonium were determined by closed core incubations, while oxygen depth profiles were recorded by microsensor profiling of sediment cores. Our results reveal a pronounced seasonality in the sedimentary oxygen consumption. Low uptake rates in summer were caused by oxygen limitation, and resulted in the build‐up of an “oxygen debt” through the accumulation of reduced iron sulfides. Highest oxygen uptake rates were recorded in fall, linked to the reoxidation of the pool of iron sulfides in the top layer. However, uptake rates remained unexpectedly high during winter and early spring, likely associated with the oxidation of iron sulfides down to centimeters depth due to the electrogenic sulfur oxidation by cable bacteria. Overall, our results suggest that the sedimentary oxygen dynamic in seasonally hypoxic coastal systems is characterized by a strongly amplified “oxygen debt” dynamics induced by cable bacteria.

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Unprecedented remote sensing data over King and Rim megafires in the Sierra Nevada Mountains of California - E. Natasha Stavros; Zachary Tane; Van R. Kane; Sander Veraverbeke; Robert J. McGaughey; James A. Lutz; Carlos Ramirez; David Schimel (Ecology, 2016)
Megafires have lasting social, ecological, and economic impacts and are increasing in the western contiguous United States. Because of their infrequent nature, there is a limited sample of megafires to investigate their unique behavior, drivers, and relationship to forest management practices. One approach is to characterize critical information pre‐, during, and post‐fire using remote sensing. In August 2013, the Rim Fire burned 104,131 ha and in September 2014, the King Fire burned 39,545 ha. Both fires occurred in California's Sierra Nevada. The areas burned by these fires were fortuitously surveyed by airborne campaigns, which provided the most recent remote sensing technologies not currently available from satellite. Technologies include an imaging spectrometer spanning the visible to shortwave infrared (0.38–2.5 μm), a multispectral, high‐spatial resolution thermal infrared (3.5–13 μm) spectroradiometer, and Light Detection and Ranging that provide spatial resolutions of pixels from 1 × 1 m to 35 × 35 m. Because of the unique information inherently derived from these technologies before the fires, the areas were subsequently surveyed after the fires. We processed and provide free dissemination of these airborne datasets as products of surface reflectance, spectral metrics and forest structural metrics ( http://dx.doi.org/10.3334/ORNLDAAC/1288 ). These data products provide a unique opportunity to study relationships among and between remote sensing observations and fuel and fire characteristics (e.g., fuel type, condition, structure, and fire severity). The novelty of these data is not only in the unprecedented types of information available from them before, during, and after two megafires, but also in the synergistic use of multiple state of the art technologies for characterizing the environment. The synergy of these data can provide novel information that can improve maps of fuel type, structure, abundance, and condition that may improve predictions of megafire behavior and effects, thus aiding management before, during, and after such events. Key questions that these data could address include: What drives, extinguishes, and results from megafires? How does megafire behavior relate to fire and fuel management? How does the size and severity of a megafire affect the ecological recovery of the system?

Ontogeny changes and weaning effects in gene expression patterns of digestive enzymes and regulatory digestive factors in spotted rose snapper (Lutjanus guttatus) larvae - I. Moguel-Hernández; R. Peña; K. B. Andree; D. Tovar-Ramirez; K. Bonacic; S. Dumas; E. Gisbert (Fish Physiology and Biochemistry, 2016)

Cryptic Caribbean species of Scorpaena (Actinopterygii: Scorpaeniformes) suggested by cytogenetic and molecular data - M. Nirchio; C. Oliveira; Z. R. Siccha‐Ramirez; V. F. Sene; O. R. Sánchez‐Romero; N. R. Ehemann; V. Milana; A. R. Rossi; L. Sola (Journal of Fish Biology, 2016)
Cytogenetic and molecular analyses enabled identification of two cytotypes among individuals of the spotted scorpion fish Scorpaena plumieri from Margarita Island, Venezuela. Cytotype 1 was characterized by 48 subtelo‐acrocentric chromosomes and fundamental number (number of chromosome arms; FN ) equalled 48, while cytotype 2 was characterized by two metacentric and 46 subtelo‐acrocentric chromosomes and FN was 50. These cytotypes also differed in the location of the ribosomal gene clusters and in the distribution of the constitutive heterochromatin. Moreover, fish from the cytotypes 1 and 2 were found to belong to distinct mitochondrial lineages. The presence of two S. plumieri cytotypes from two lineages separated by high genetic distance suggests that they correspond to sympatric cryptic species.

Variation in spatial scale of competing polydomous twig-nesting ants in coffee agroecosystems - K. A. Mathis; S. M. Philpott; S. R. Ramirez (Insectes Sociaux, 2016)

Cell-free mitochondrial DNA in CSF is associated with early viral rebound, inflammation, and severity of neurocognitive deficits in HIV infection - Josué Pérez-Santiago; Rachel D. Schrier; Michelli F. de Oliveira; Sara Gianella; Susanna R. Var; Tyler R. C. Day; Miguel Ramirez-Gaona; Jesse D. Suben; Ben Murrell; Marta Massanella; Mariana Cherner; Davey M. Smith; et al. (Journal of NeuroVirology, 2016)

Persistence of a single clone of Streptococcus agalactiae causing disease in tilapia ( Oreochromis sp.) cultured in Colombia over 8 years - P Barato; E R Martins; J Melo‐Cristino; C A Iregui; M Ramirez (Journal of Fish Diseases, 2015)

Mapping a Type 1 FHB resistance on chromosome 4AS of Triticum macha and deployment in combination with two Type 2 resistances - C. Burt; A. Steed; N. Gosman; M. Lemmens; N. Bird; R. Ramirez-Gonzalez; S. Holdgate; P. Nicholson (Theoretical and Applied Genetics, 2015)

Physiological and biochemical response of soil-grown barley (Hordeum vulgare L.) to cerium oxide nanoparticles - Cyren M. Rico; Ana C. Barrios; Wenjuan Tan; Rosnah Rubenecia; Sang Chul Lee; Armando Varela-Ramirez; Jose R. Peralta-Videa; Jorge L. Gardea-Torresdey (Environmental Science and Pollution Research, 2015)

Anuran trypanosomes: phylogenetic evidence for new clades in Brazil - Juliana I. G. da S. Ferreira; Andrea P. da Costa; Diego Ramirez; Jairo A. M. Roldan; Danilo Saraiva; Gislene F. R. da S. Founier; Ana Sue; Erick R. Zambelli; Antonio H. H. Minervino; Vanessa K. Verdade; Solange M. Gennari; Arlei Marcili (Systematic Parasitology, 2015)

Stem Nematode Counteracts Plant Resistance of Aphids in Alfalfa, Medicago Sativa - Ricardo A. Ramirez; Lori R. Spears (Journal of Chemical Ecology, 2014)

Improving Environmental and Social Targeting through Adaptive Management in Mexico's Payments for Hydrological Services Program - KATHARINE R. E. SIMS; JENNIFER M. ALIX‐GARCIA; ELIZABETH SHAPIRO‐GARZA; LEAH R. FINE; VOLKER C. RADELOFF; GLEN ARONSON; SELENE CASTILLO; CARLOS RAMIREZ‐REYES; PATRICIA YAÑEZ‐PAGANS (Conservation Biology, 2014)
Natural resource managers are often expected to achieve both environmental protection and economic development even when there are fundamental trade‐offs between these goals. Adaptive management provides a theoretical structure for program administrators to balance social priorities in the presence of trade‐offs and to improve conservation targeting. We used the case of Mexico's federal Payments for Hydrological Services program (PSAH) to illustrate the importance of adaptive management for improving program targeting. We documented adaptive elements of PSAH and corresponding changes in program eligibility and selection criteria. To evaluate whether these changes resulted in enrollment of lands of high environmental and social priority, we compared the environmental and social characteristics of the areas enrolled in the program with the characteristics of all forested areas in Mexico, all areas eligible for the program, and all areas submitted for application to the program. The program successfully enrolled areas of both high ecological and social priority, and over time, adaptive changes in the program's criteria for eligibility and selection led to increased enrollment of land scoring high on both dimensions. Three factors facilitated adaptive management in Mexico and are likely to be generally important for conservation managers: a supportive political environment, including financial backing and encouragement to experiment from the federal government; availability of relatively good social and environmental data; and active participation in the review process by stakeholders and outside evaluators. Mejorando los Objetivos Ambiental y Social Mediante el Manejo Adaptativo en el Programa de Pagos por Servicios Hidrológicos en México

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

The Gender of Cell Lines Matters When Screening for Novel Anti-Cancer Drugs - Larissa M. Nunes; Elisa Robles-Escajeda; Yahaira Santiago-Vazquez; Nora M. Ortega; Carolina Lema; Almendra Muro; Gladys Almodovar; Umashankar Das; Swagatika Das; Johnatan R. Dimmock; Renato J. Aguilera; Armando Varela-Ramirez (The AAPS Journal, 2014)

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Mortality of resprouting chaparral shrubs after a fire and during a record drought: physiological mechanisms and demographic consequences - R. Brandon Pratt; Anna L. Jacobsen; Aaron R. Ramirez; Anjel M. Helms; Courtney A. Traugh; Michael F. Tobin; Marcus S. Heffner; Stephen D. Davis (Global Change Biology, 2014)
We examined postfire regeneration of chaparral shrubs during an intense drought. This study focused on the demography and physiology of shrub species that resprout from a basal lignotuber following fire. We found significant levels of resprout mortality when intense drought occurred in the year following fire during the period of shrub recovery. Three of the seven sampled resprouting species had the greatest or near greatest levels of mortality ever recorded when compared to previous studies. Most shrub mortality occurred during the drought after individuals had resprouted (i.e. individuals survived fire, resprouted and then subsequently died). Physiological measurements of species with high mortality suggested that resprout stems were highly embolized and xylem hydraulic conductivities were close to zero during the peak of the drought. In addition, lignotubers of two of the three species experiencing high mortality were depleted of starch. Population densities of most shrub species declined after the drought compared with their prefire levels, with the exception of one drought tolerant obligate seeding species. Resprouting shrub species may deplete their carbohydrate reserves during the resprouting process, making them particularly vulnerable to drought because of the need to transpire water to acquire the CO 2 that is used to supply energy to a large respiring root system. Drought appears to interact with fire by altering postfire shrub recovery and altering species abundances and composition of chaparral communities.

Comparison of static and dynamic respirometry for the determination of stoichiometric and kinetic parameters of a nitrifying process - R. Ramirez-Vargas; A. Ordaz; M. Carrión; I. Y. Hernández-Paniagua; F. Thalasso (Biodegradation, 2013)

Xenobiotic metabolizing enzyme activities in cells used for testing skin sensitization in vitro - E. Fabian; D. Vogel; V. Blatz; T. Ramirez; S. Kolle; T. Eltze; B. van Ravenzwaay; F. Oesch; R. Landsiedel (Archives of Toxicology, 2013)

The Reciprocal Cerebellar Circuitry in Human Hereditary Ataxia - Arnulf H. Koeppen; R. Liane Ramirez; Sarah T. Bjork; Peter Bauer; Paul J. Feustel (The Cerebellum, 2013)

Predictors of regional establishment success and spread of introduced non‐indigenous vertebrates - Craig R. Allen; Kristine T. Nemec; Donald A. Wardwell; Justin D. Hoffman; Mathew Brust; Karie L. Decker; Daniel Fogell; Jennifer Hogue; Aaron Lotz; Thaddeus Miller; Marcy Pummill; Luis E. Ramirez‐Yañez; et al. (Global Ecology and Biogeography, 2013)
Aim To provide the first analysis of predictors of both establishment and spread, both within and across taxa, for all vertebrate taxa within a region. We used F lorida, USA , as our study system because it has a well‐documented history of introduction and invasion, and is a hotspot for biological invasions. Location F lorida, USA. Methods We analysed non‐indigenous species ( NIS ) data from peninsular F lorida – which included both successful and unsuccessful introductions from all vertebrate classes – to determine the best predictors of both establishment and spread for fish (65 species), herpetofauna (63 species), birds (71 species) and mammals (25 species). We used 10 variables proposed to be associated with the establishment and spread of NIS : body mass, geographic origin, reproductive rate, diet generalism, native‐range size, latitude of native range, number of NIS present at date of introduction, presence of NIS congeners, morphological proximity to other NIS (in terms of body mass) and propagule pressure. A multimodel selection process was used with an information‐theoretic approach to determine the best fit models for predicting establishment and spread of NIS . We selected a priori plausible predictive models for establishment and spread. Results Large native‐range size and small body mass best predicted establishment of non‐indigenous herpetofauna. The presence of NIS congeners had the largest positive effect on the establishment of non‐indigenous fish. For mammals, the number of NIS present at the time of introduction best explained establishment. No single model best explained bird establishment. For all taxa but birds, the number of NIS present at time of introduction was included in at least one of the best‐supported models for explaining spread. Main conclusions Our analyses suggest that predictors of establishment and spread differ across vertebrate taxa at the scale studied. Most predictive variables can be interpreted as measures of competitive interactions among species.

Technique for Restoration of Mite (Acari) Preparations in Deteriorated Hoyer’s Medium - F C Jacinavicius; J C Badari; D G Ramirez; R H P Moraes; V C Onofrio; D M Barros-Battesti (Neotropical Entomology, 2013)

Incidence of respiratory viruses in patients with community-acquired pneumonia admitted to the intensive care unit: results from the Severe Influenza Pneumonia Surveillance (SIPS) project - T. Wiemken; P. Peyrani; K. Bryant; R. R. Kelley; J. Summersgill; F. Arnold; R. Carrico; W. P. McKinney; C. Jonsson; K. Carrico; J. Ramirez (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Influence of human immune cells on cancer: studies at the University of Colorado - Tullia C. Bruno; Jena D. French; Kimberly R. Jordan; Oscar Ramirez; Trisha R. Sippel; Virginia F. Borges; Bryan R. Haugen; Martin D. McCarter; Allen Waziri; Jill E. Slansky (Immunologic Research, 2013)

Superantigen gene complement of Streptococcus pyogenes—relationship with other typing methods and short-term stability - A. Friães; F. R. Pinto; C. Silva-Costa; M. Ramirez; J. Melo-Cristino (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Friedreich's Ataxia Causes Redistribution of Iron, Copper, and Zinc in the Dentate Nucleus - Arnulf H. Koeppen; R. Liane Ramirez; Devin Yu; Sarah E. Collins; Jiang Qian; Patrick J. Parsons; Karl X. Yang; Zewu Chen; Joseph E. Mazurkiewicz; Paul J. Feustel (The Cerebellum, 2012)

Vertical density gradient in the eastern North Atlantic during the last 30,000 years - M. Rogerson; G. R. Bigg; E. J. Rohling; J. Ramirez (Climate Dynamics, 2012)

Exotic deer diminish post-fire resilience of native shrub communities on Santa Catalina Island, southern California - A. R. Ramirez; R. B. Pratt; A. L. Jacobsen; S. D. Davis (Plant Ecology, 2012)

General analysis of competitive binding in drug–interceptor–DNA systems - A. S. Buchelnikov; A. A. Hernandez Santiago; M. Gonzalez Flores; R. Vazquez Ramirez; D. B. Davies; M. P. Evstigneev (European Biophysics Journal, 2012)

Changes in partial pressures of respiratory gases during submerged voluntary breath hold across odontocetes: is body mass important? - S. R. Noren; T. M. Williams; K. Ramirez; J. Boehm; M. Glenn; L. Cornell (Journal of Comparative Physiology B, 2012)

A comparative analysis of microflora during biofilm development on grape seeds exposed to methanol in a biofilter - R. Moreno-Terrazas; F. J. Flores-Tena; M. D. Barba-Avila; A. L. Guerrero-Barrera; F. J. Avelar-Gonzalez; E. M. Ramirez-Lopez (World Journal of Microbiology and Biotechnology, 2010)

Effects of mGluR1 antagonism in the dorsal hippocampus on drug context-induced reinstatement of cocaine-seeking behavior in rats - Xiaohu Xie; Donna R. Ramirez; Heather C. Lasseter; Rita A. Fuchs (Psychopharmacology, 2010)

Multivariate analysis of the energy cycle of the South American rainy season - Enver Ramirez Gutierrez; P. L. Silva Dias; J. A. Veiga; R. Camayo; A. dos Santos (International Journal of Climatology, 2009)
The South American (SA) rainy season is studied in this paper through the application of a multivariate Empirical Orthogonal Function (EOF) analysis to a SA gridded precipitation analysis and to the components of Lorenz Energy Cycle (LEC) derived from the National Centers for Environmental Prediction (NCEP) reanalysis. The EOF analysis leads to the identification of patterns of the rainy season and the associated mechanisms in terms of their energetics. The first combined EOF represents the northwest–southeast dipole of the precipitation between South and Central America, the South American Monsoon System (SAMS). The second combined EOF represents a synoptic pattern associated with the SACZ (South Atlantic convergence zone) and the third EOF is in spatial quadrature to the second EOF. The phase relationship of the EOFs, as computed from the principal components (PCs), suggests a nonlinear transition from the SACZ to the fully developed SAMS mode by November and between both components describing the SACZ by September–October (the rainy season onset). According to the LEC, the first mode is dominated by the eddy generation term at its maximum, the second by both baroclinic and eddy generation terms and the third by barotropic instability previous to the connection to the second mode by September–October. The predominance of the different LEC components at each phase of the SAMS can be used as an indicator of the onset of the rainy season in terms of physical processes, while the existence of the outstanding spectral peaks in the time dependence of the EOFs at the intraseasonal time scale could be used for monitoring purposes. Copyright © 2009 Royal Meteorological Society

Monocyte Chemotactic Protein-1 Regulates Voltage-Gated K+ Channels and Macrophage Transmigration - Howard E. Gendelman; Shengyuan Ding; Nan Gong; Jianuo Liu; Servio H. Ramirez; Yuri Persidsky; R. Lee Mosley; Tong Wang; David J. Volsky; Huangui Xiong (Journal of Neuroimmune Pharmacology, 2009)

Widespread expression of inducible NOS and citrulline in lupus nephritis tissues - J. J. Bollain-y-Goytia; R. Ramírez-Sandoval; L. Daza; E. Esparza; O. Barbosa; D. Ramirez; G. Pacheco-Tovar; E. Avalos-Diaz; C. Rodríguez-Padilla; R. Herrera-Esparza (Inflammation Research, 2009)

Nucleus accumbens shell and core involvement in drug context-induced reinstatement of cocaine seeking in rats - Rita A. Fuchs; Donna R. Ramirez; Guinevere H. Bell (Psychopharmacology, 2008)

Hypercalcemia due to an interaction of all-trans retinoic acid (ATRA) and itraconazole therapy for acute promyelocytic leukemia successfully treated with zoledronic acid - R. Cordoba; E. Ramirez; S. H. Lei; A. Lopez de la Guia; M. J. Sanjurjo; A. J. Carcas; F. Hernandez-Navarro (European Journal of Clinical Pharmacology, 2008)

Migratory movements and surfacing rates of humpback whales ( Megaptera novaeangliae ) satellite tagged at Socorro Island, Mexico - Barbara A. Lagerquist; Bruce R. Mate; Joel G. Ortega‐Ortiz; Martha Winsor; Jorge Urbán‐Ramirez (Marine Mammal Science, 2008)
Humpback whales wintering in the Revillagigedo Archipelago, Mexico, have been considered a different subpopulation from those found off mainland Mexico and Baja California. The primary feeding grounds for Revillagigedo humpbacks remain unknown. In February 2003, we deployed 11 Argos satellite‐monitored radio tags to track movements and surfacings of humpback whales (five adults without calves, five mothers with calves, one calf) off Socorro Island in the Revillagigedo Archipelago. Tracking ranged from 222 to 10,481 km over 4.9–149.1 d. Eight whales left Socorro Island: five visited other Mexican wintering destinations, seven moved north of these areas. Migration routes were primarily offshore (average 444 km). Two whales were tracked to feeding grounds: one to British Columbia (46 d migration), and one to Alaska (49 d migration). Mean travel speeds were 1.2 km/h in wintering areas, 4.0 km/h during migration, and 2.2 km/h in feeding areas. Overall surfacing rates ranged from 21 to 88 surfacings/h. Surfacing rates differed between the calf and all other whales, and between feeding areas and migratory/wintering areas for the calf and an adult without a calf. The calf also showed diel variation in surfacing rates. The offshore habits of tagged whales may explain scarce resightings of Revillagigedo humpbacks outside the Revillagigedo Archipelago.

Selective Contrast Enhancement of Individual Alzheimer’s Disease Amyloid Plaques Using a Polyamine and Gd-DOTA Conjugated Antibody Fragment Against Fibrillar Aβ42 for Magnetic Resonance Molecular Imaging - Muthu Ramakrishnan; Thomas M. Wengenack; Karunya K. Kandimalla; Geoffry L. Curran; Emily J. Gilles; Marina Ramirez-Alvarado; Joseph Lin; Michael Garwood; Clifford R. Jack Jr.; Joseph F. Poduslo (Pharmaceutical Research, 2008)

Changes in chromosome organization during PHA-activation of resting human lymphocytes measured by cryo-FISH - Miguel R. Branco; Tiago Branco; Francisco Ramirez; Ana Pombo (Chromosome Research, 2008)

Polymorphism in the Matrix Metalloproteinase-2 Gene Promoter is Associated with Cervical Neoplasm Risk in Mexican Women - Luz M. Baltazar-Rodriguez; Aristoteles Anaya-Ventura; Maricela Andrade-Soto; Elisa A. Monrroy-Guizar; Jose R. Bautista-Lam; Gregorio Jonguitud-Olguin; Friedman R. Cepeda-Lopez; Veronica A. Centeno-Aguilar; Nelida A. Gonzalez-Hernandez; Alejandro D. Soriano-Hernández; Mario Ramirez-Flores; Angel Lugo-Trampe; et al. (Biochemical Genetics, 2008)

In vitro propagation of ten threatened species of Mammillaria (Cactaceae) - R. Ramirez-Malagon; I. Aguilar-Ramirez; A. Borodanenko; L. Perez-Moreno; J. L. Barrera-Guerra; H. G. Nuñez-Palenius; N. Ochoa-Alejo (In Vitro Cellular & Developmental Biology - Plant, 2007)

Comparative phylogeography of Trypanosoma rangeli and Rhodnius (Hemiptera: Reduviidae) supports a long coexistence of parasite lineages and their sympatric vectors - F. MAIA DA SILVA; A. C. V. JUNQUEIRA; M. CAMPANER; A. C. RODRIGUES; G. CRISANTE; L. E. RAMIREZ; Z. C. E. CABALLERO; F. A. MONTEIRO; J. R. COURA; N. AÑEZ; M. M. G. TEIXEIRA (Molecular Ecology, 2007)
To make reliable interpretations about evolutionary relationships between Trypanosoma rangeli lineages and their insect vectors (triatomine bugs of the genus Rhodnius ) and, thus, about the determinant factors of lineage segregation within T. rangeli , we compared phylogenies of parasite isolates and vector species. Sixty‐one T. rangeli isolates from invertebrate and vertebrate hosts were initially evaluated in terms of polymorphism of the spliced‐leader gene (SL). Further analysis based on SL and SSUrRNA sequences from 33 selected isolates, representative of the overall phylogenetic diversity and geographical range of T. rangeli , supported four phylogenetic lineages within this species. By comparing the phylogeny of Rhodnius species with that inferred for T. rangeli isolates and through analysis of the geographical range of the isolates, we showed that there is a very significant overlap in the distribution of Rhodnius species and T. rangeli lineages. Congruence between phylogeographical analysis of both T. rangeli lineages and complexes of Rhodnius species are consistent with the hypothesis of a long coexistence of parasites and their vectors, with lineage divergence associated with sympatric species of Rhodnius apparently without association with particular vertebrate hosts. Separation of T. rangeli isolates from vectors of distinct complexes living in sympatry favours the absence of gene flow between the lineages and suggests evolution of T. rangeli lineages in independent transmission cycles, probably associated to specific Rhodnius spp. ecotopes. A polymerase chain reaction assay based on SL intergenic sequences was developed for simultaneous identification and lineage genotyping of T. rangeli in epidemiological surveys.

Functional analysis of Arabidopsis genes involved in mitochondrial iron–sulfur cluster assembly - Ana Paula Guedes Frazzon; Melissa V. Ramirez; Ujwala Warek; Janneke Balk; Jeverson Frazzon; Dennis R. Dean; Brenda S. J. Winkel (Plant Molecular Biology, 2007)

N terminus determinants of MinC from Neisseria gonorrhoeae mediate interaction with FtsZ but do not affect interaction with MinD or homodimerization - V. Greco-Stewart; S. Ramirez-Arcos; M. Liao; J. R. Dillon (Archives of Microbiology, 2007)

Diversity of human rotaviruses detected in Sicily, Italy, over a 5-year period (2001–2005) - S. De Grazia; S. Ramirez; G. M. Giammanco; C. Colomba; V. Martella; C. Lo Biundo; R. Mazzola; S. Arista (Archives of Virology, 2007)

Multisensory processing and oscillatory activity: analyzing non-linear electrophysiological measures in humans and simians - Daniel Senkowski; Manuel Gomez-Ramirez; Peter Lakatos; Glenn R. Wylie; Sophie Molholm; Charles E. Schroeder; John J. Foxe (Experimental Brain Research, 2007)

Anti-tumor necrosis factor α F(ab')2 antibody fragments protect in murine polymicrobial sepsis: Concentration and early intervention are fundamental to the outcome - R. Márquez-Velasco; R. Bojalil; A. Buelna; F. Flores-Guzmán; J. Estevez-Ramirez; J. Laguna; A. M. Hernández; A. Díaz-Quiñonez; J. F. Paniagua-Solís (Inflammation Research, 2006)

Predictability of littoral-zone fish communities through ontogeny in Lake Texoma, Oklahoma-Texas, USA - Michael A. Eggleton; Raul Ramirez; Chad W. Hargrave; Keith B. Gido; Jason R. Masoner; Gary D. Schnell; William J. Matthews (Environmental Biology of Fishes, 2005)

In vitro cytoskeleton changes of mouse neurons induced by purified HTLV-1, and PBMC from HAM/TSP patients and HTLV-1 carriers - E. Ramirez; L. Cartier; R. Flores (Archives of Virology, 2004)

Glaciers and Climate in the Andes between the Equator and 30° S: What is Recorded under Extreme Environmental Conditions? - U. Schotterer; M. Grosjean; W. Stichler; P. Ginot; C. Kull; H. Bonnaveira; B. Francou; H. W. Gäggeler; R. Gallaire; G. Hoffmann; B. Pouyaud; E. Ramirez; et al. (Climatic Change, 2003)

Refining the Whooping Crane Studbook by Incorporating Microsatellite DNA and Leg‐Banding Analyses - Kenneth L. Jones; Travis C. Glenn; Robert C. Lacy; James R. Pierce; Natalie Unruh; Claire M. Mirande; Felipe Chavez‐Ramirez (Conservation Biology, 2002)
We sought to refine genetic management of the endangered Whooping Crane ( Grus americana ) population by developing comprehensive genetic pedigrees for the captive population. Improvements to the studbook were accomplished by addition of pedigree information derived from leg‐banding data on wild juvenile and founder similarity coefficients calculated from microsatellite DNA profiles to the original studbook pedigree. Incorporation of pedigrees derived from data on leg‐banding of wild juveniles did not greatly alter the previous relatedness structure of the captive population, but incorporation of microsatellite similarity coefficients produced a substantially different view of the population structure. Microsatellite data provided new information on shared founder genotypes and provided a new DNA–based studbook pedigree that will assist in genetic management of the Whooping Crane population.

Etoposide-induced apoptosis in lymphoblastoid leukaemic MOLT-4 cells: Evidence that chromatin condensation, loss of phosphatidylserine asymmetry and apoptotic body formation can occur independently - C. D. Ramirez; D. R. Catchpoole (Apoptosis, 2002)

Control of Cell pH in the T84 Colon Cell Line - M.A. Ramirez; R. Toriano; M. Parisi; G. Malnic (The Journal of Membrane Biology, 2000)

Permeation of NH3/NH4 + and cell pH in colonic crypts of the rat - M. Ramirez; R. Fernandez; G. Malnic (Pflügers Archiv - European Journal of Physiology, 1999)

Permeation of NH 3 /NH 4 + and cell pH in colonic crypts of the rat - M. Ramirez; R. Fernandez; G. Malnic (Pflügers Archiv - European Journal of Physiology, 1999)

Production of volatile compounds by the edible fungus Rhizopus oryzae during solid state cultivation on tropical agro-industrial substrates - Adriana Bramorski; Pierre Christen; Martha Ramirez; Carlos R. Soccol; Sergio Revah (Biotechnology Letters, 1998)

Comparison of Colombian and Costa Rican Strains of Rice Hoja Blanca Tenuivirus - Joachim R. De Miranda; Bertha-Cecilia Ramirez; Miguel Mun~oz; Ivan Lozano; Ray Wu; Anne-Lise Haenni; Ana M. Espinoza; Lee A. Calvert (Virus Genes, 1997)

Repopulation and culture of the Pacific Calico scallops in Bahia Concepcion, Baja California Sur, Mexico - E.F. Felix-Pico; A. Tripp-Quezada; J.L. Castro-Ortiz; G. Serrano-Casillas; P.G. Gonzalez-Ramirez; M. Villalejo-Fuerte; R. Palomares-Garcia; F.A. Garcia-Dominguez; M. Mazon-Suastegui; G. Bojorquez-Verastica; G. Lopez-Garcia (Aquaculture International, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Electron probe X-ray microanalysis of arsenic inclusions in fish - Elsie M. B. Sorensen; Nancy K. R. Smith; Ruben Ramirez-Mitchell (Archives of Environmental Contamination and Toxicology, 1982)